Analysis of Institutional Quality Influence on Shadow Economy Development - Maulida, Rahma Hanii; Darwanto, Darwanto (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
GDP is the main indicator of economy which reflects economic activities in a country. In fact, shadow economy is exist in every country, it is some of the activities which are not included in the national account. This condition can lead to a biased policies. So that, it is important to take into account the shadow economy when formulating policies. There are no such of data for shadow economy activities. The purpose of this research is to estimate shadow economy in seven developing countries of ASEAN. The estimation method used is the MIMIC approach in the period of 2007-2016. Besides, this research also examines the influence of the institutional quality on the shadow economy development. The results show that shadow economy in ASEAN has increased since 2007. Thailand is a country with the largest shadow economy among the ASEAN member countries with an average of 46.84% of GDP. On the other hand, the institutional quality shows a negative relationship with the development of shadow economy, except regulatory quality. Variables of control of corruption, political stability and absence of violent, and voice and accountability have influence on reducing the shadow economy development.